PENGARUH RASIO KEUANGAN DAN KEPEMILIKAN MANAJERIAL UNTUK MEMPREDIKSI FINANSIAL DISTRESS PADA PERUSAHAAN TRANSPORTASI DAN PARIWISATA SAAT PANDEMI COVID-19 YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Amita Nur Rahma; Nur Hayati (Universitas Budi Luhur, 2022)
This study aims to determine how much influence profitability, liquidity, leverage, and managerial ownership have on financial distress in transportation and tourism companies during the Covid-19 pandemic listed on Bursa Efek Indonesia (BEI). This study relied on secondary data from 50 samples collected between 2019 and 2020. This study employs quantitative descriptive research. To demonstrate the study's hypothesis, multiple linear regression models and the t-test were used. According to the data analysis results, the variables of profitability, liquidity, and Leverage all have a significant effect on financial distress, while managerial ownership variables have no effect on financial distress.